2011
DOI: 10.1590/s0100-204x2011000800013
|View full text |Cite
|
Sign up to set email alerts
|

Estratificação ambiental pela análise da interação genótipo x ambiente em milho

Abstract: Resumo -O objetivo deste trabalho foi realizar a estratificação de ambientes de cultivo de milho nos Estados do Paraná, Minas Gerais e Bahia, por diferentes métodos, bem como determinar o grau de associação e divergência entre os métodos de estratificação. Foram avaliados quatro métodos: o tradicional de Lin; o de dissimilaridade ambiental; o de decomposição da interação genótipo x ambiente (GxA) em partes simples e complexa; e o de análise de fatores. Esses métodos foram aplicados a 48 híbridos experimentais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
2
10
0
5
Order By: Relevance
“…Garbuglio et al (2007) broke down the interaction in simple and complex parts for all the pairs of environments and observed that the environments grouped in the same factor contained a large part of the interaction as simple. These results were also observed by Mendonça et al (2007) and Ribeiro and Almeida (2011). These results confirm the efficiency of the groupings obtained via factor analyses after rotation.…”
Section: Factor Analysis Of the G+ge Matrixsupporting
confidence: 85%
See 3 more Smart Citations
“…Garbuglio et al (2007) broke down the interaction in simple and complex parts for all the pairs of environments and observed that the environments grouped in the same factor contained a large part of the interaction as simple. These results were also observed by Mendonça et al (2007) and Ribeiro and Almeida (2011). These results confirm the efficiency of the groupings obtained via factor analyses after rotation.…”
Section: Factor Analysis Of the G+ge Matrixsupporting
confidence: 85%
“…This result may be observed in Table 3, where analysis with two factors grouped 4 environments on the first axis and 3 on the second axis and, in the other situations, there was no grouping but rather a scattering of the environments among the axes. Fritsche-Neto et al (2010b) and Ribeiro and Almeida (2011) obtained similar results, in which environments were spread out by the factors and, as a result, no grouping was obtained.…”
Section: Factor Analysis Of the G+ge Matrixmentioning
confidence: 65%
See 2 more Smart Citations
“…The maize breeding encouters interference of G × E interaction, such as the difficulty of finding the bests genotypes, phenotypic stability and adaptability, the nature of the interaction of simple or complex and a differential answer of the characters that determinate the potencial productive of the culture (Ribeiro and Almeida, 2011). Conversely, some researches have pointed out that the grains mass, the ear dimensions, grains number per plant (Lopes et al, 2007), the plant stature , the prolificity (De Carvalho et al, 2001), the number of grains per ear rows (Balbinot et al, 2005) are determinant to increase the grains yield in maize.…”
Section: Introductionmentioning
confidence: 99%